Asylum-seeking children in shutdown: Neurobiological models. (September 2021) - Kozlowska, Kasia; Scher, Stephen; Helgeland, Helene; Carrive, Pascal
Asylum-seeking children presenting in the shutdown state have been the subject of much discussion and controversy—on both government and medical system levels—in Australia and in Sweden. In this article, we conceptualize the shutdown state as an evolutionary response to extreme threat. We adopt a neuroscience approach to present five plausible models for explaining this shutdown state, their strengths and shortcomings, and the overlaps between them. Model 1—the sustained autonomic arousal model—draws on polyvagal theory. Model 2—the innate-defence model—draws on research pertaining to animal and human innate defence responses. Model 3—the catatonia model—draws on clinical and research data with patients presenting with catatonia. Model 4—the hypometabolic model—draws on an emerging body of work pertaining to hypometabolic states in animals and humans. Model 5—the defence cascade model of dissociation—draws on clinical research pertaining to human trauma states that present as dissociation. At present, each of the models provides a plausible pathophysiological explanation—or a component of a potential pathophysiological explanation—and none of them, for the moment, has enough evidence to be either accepted or disregarded. We hope that our discussion of the models advances scientific discussion and opens up possibilities for effective treatment.